Assessment Practices of Elementary School Teachers Based on Competency Mapping: An Equity-Oriented Perspective for Supporting Deep Learning - Nasib Wasito; Herpratiwi (Women, Education, and Social Welfare, 2026)
Assessment and feedback play a critical role in supporting meaningful learning and promoting students’ higher-order thinking skills; however, many elementary school teachers continue to experience difficulties in designing student-centered assessments that support deep learning processes. This study aims to analyze elementary school teachers’ assessment practices based on competency mapping within a deep learning perspective and an equity-oriented framework of teacher professional development. The study employed a quantitative descriptive approach using secondary data from teacher competency mapping conducted by Balai GTK Lampung in 2025 involving 19,384 elementary school teachers. Data were analyzed using descriptive statistical techniques to examine the distribution of pedagogical competencies, particularly in the assessment domain. The findings indicate that teachers demonstrate relatively adequate competence in establishing safe learning environments and implementing student-centered learning, while competencies related to formative assessment design and feedback provision remain comparatively lower than other pedagogical domains. These results suggest that assessment literacy supporting deep learning has not yet been optimally implemented in elementary classrooms and requires targeted professional development interventions. From an inclusive education perspective, strengthening assessment competence is essential for improving equitable classroom participation and supporting teachers’ instructional agency and professional wellbeing. This study contributes to the literature by providing large-scale competency mapping evidence on teachers’ assessment practices and highlighting assessment literacy as a strategic component of welfare-oriented and equity-responsive teacher development aligned with Sustainable Development Goals 4 and 5.